2022
DOI: 10.1155/2022/2942918
|View full text |Cite
|
Sign up to set email alerts
|

Delivering the National Diabetes Prevention Program: Assessment of Enrollment in In-Person and Virtual Organizations

Abstract: The aim of the US Centers for Disease Control and Prevention’s (CDC) National Diabetes Prevention Program (National DPP) is to make an evidence-based lifestyle change program widely available to the more than 88 million American adults at risk for developing type 2 diabetes. The National DPP allows for program delivery using four delivery modes: in person, online, distance learning, and combination. The objective of this study was to analyze cumulative enrollment in the National DPP by delivery mode. We includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…In both rural and urban communities, individuals at highest risk of type 2 diabetes—men, Medicare beneficiaries, Latinos, African Americans, and individuals from other racial and ethnic groups— were under-enrolling in CDC-recognized lifestyle change programs. 4 For some, it was a basic access issue—the closest program was hours away— whereas for others, it was a more complicated interplay between social determinants of health challenges, cultural disconnection, lack of awareness, and cost that kept them from enrolling in a National DPP lifestyle change program.…”
Section: From Graphs To Mapsmentioning
confidence: 99%
See 1 more Smart Citation
“…In both rural and urban communities, individuals at highest risk of type 2 diabetes—men, Medicare beneficiaries, Latinos, African Americans, and individuals from other racial and ethnic groups— were under-enrolling in CDC-recognized lifestyle change programs. 4 For some, it was a basic access issue—the closest program was hours away— whereas for others, it was a more complicated interplay between social determinants of health challenges, cultural disconnection, lack of awareness, and cost that kept them from enrolling in a National DPP lifestyle change program.…”
Section: From Graphs To Mapsmentioning
confidence: 99%
“…With every variant, there was another spike of cases and more exponential graphs as we observed this novel coronavirus spreading rapidly within our own neighborhoods, cities, counties, and states. 4 For some, it was a basic access issue-the closest program was hours awaywhereas for others, it was a more complicated interplay between social determinants of health challenges, cultural disconnection, lack of awareness, and cost that kept them from enrolling in a National DPP lifestyle change program.…”
mentioning
confidence: 99%
“…10 Increasing enrollment in the DPP is an ongoing challenge, but digital health offerings improve the availability of accessible programs by meeting participants when and where they need assistance. [11][12][13] Digital solutions can also improve the personalization of coaching interactions through the large volume of data they collect from members and the frequent feedback delivery and reminders made possible via automation. 14 Participation in a digital DPP can improve both individual health through disease prevention and save the healthcare system substantial medical costs by reducing the incidence of T2D and its associated complications.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that individuals at high risk for diabetes who are not enrolled in a lifestyle modification program like the National Diabetes Prevention Program (DPP) gain ∼0.42 kg per year 10 . Increasing enrollment in the DPP is an ongoing challenge, but digital health offerings improve the availability of accessible programs by meeting participants when and where they need assistance 11–13 . Digital solutions can also improve the personalization of coaching interactions through the large volume of data they collect from members and the frequent feedback delivery and reminders made possible via automation 14 …”
Section: Introductionmentioning
confidence: 99%
“…The CDC has made great strides in scaling and sustaining the National DPP. 7 However, expanding enrollment in the lifestyle change program remains a priority. 8 Offering a “session zero” is one promising strategy to increase engagement in the National DPP lifestyle change program and other chronic disease programs.…”
mentioning
confidence: 99%